European Lobster Larval Development and Fitness Under a Temperature Gradient and Ocean Acidification - Leiva, Laura; Tremblay, Nelly; Torres, Gabriela; Boersma, Maarten; Krone, Roland; Giménez, Luis (Frontiers in Physiology, 2022)
Climate change combined with anthropogenic stressors (e.g. overfishing, habitat destruction) may have particularly strong effects on threatened populations of coastal invertebrates. The collapse of the population of European lobster (Homarus gammarus) around Helgoland constitutes a good example and prompted a large-scale restocking program. The question remains if recruitment of remaining natural individuals and program-released specimens could be stunted by ongoing climate change. We examined the joint effect of ocean warming and acidification on survival, development, morphology, energy metabolism and enzymatic antioxidant activity of the larval stages of the European lobster. Larvae from four independent hatches were reared from stage I to III under a gradient of ten seawater temperatures (13-24°C) combined with moderate ( 470 µatm) and elevated ( 1160 µatm) seawater pCO2 treatments. Those treatments correspond to the shared socio-economic pathways (SSP), SSP1-2.6 and SSP5-8.5 (i.e. the low and the very high greenhouse gas emissions respectively) projected for 2100 by the Intergovernmental Panel on Climate Change. Larvae in CO2 – acidified seawater had not only lower survival rates, but also significantly smaller rostrum length. However, temperature was the main driver of energy demands with increased oxygen consumption rates and elemental C:N ratio towards warmer temperatures, with a reducing effect on development time. Using this large temperature gradient, we provide a more precise insight on the aerobic thermal window trade-offs of lobster larvae and whether exposure to the worst hypercapnia scenario may narrow it. This may have repercussions on the recruitment of the remaining natural and program-released specimens and thus, in the enhancement success of future lobster stocks.